2019
DOI: 10.1016/j.jaut.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

DNGR1-mediated deletion of A20/Tnfaip3 in dendritic cells alters T and B-cell homeostasis and promotes autoimmune liver pathology

Abstract: Dendritic cells (DCs) are central regulators of tolerance versus immunity. The outcome depends amongst others on DC subset and activation status. Whereas CD11b + type 2 conventional DCs (cDC2s) initiate proinflammatory helper T (Th)-cell responses, CD103 + cDC1s are crucial for regulatory T-cell (Treg) induction and CD8 + T-cell activation. DC activation is controlled by the transcription factor NF-κB. Ablation of A20/Tnfaip3, a critical regulator of NF-κB activation, in DCs leads to constitutive DC activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…160 B cell-specific knockout mice exhibit mild autoimmune disease, whereas dendritic cell specific deletion of A20 induces severe spontaneous inflammation. [161][162][163] 5.4 RELA proto-oncogene RELA (p65) is a NF-B family members that together with NFKB1 it constitutes the predominant canonical NF-B dimer. 7 The NFKB1/RELA heterodimer is also the primary target of I B , ensuring its cytoplasmic localization and thereby its inert state.…”
Section: Tnf Alpha Induced Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…160 B cell-specific knockout mice exhibit mild autoimmune disease, whereas dendritic cell specific deletion of A20 induces severe spontaneous inflammation. [161][162][163] 5.4 RELA proto-oncogene RELA (p65) is a NF-B family members that together with NFKB1 it constitutes the predominant canonical NF-B dimer. 7 The NFKB1/RELA heterodimer is also the primary target of I B , ensuring its cytoplasmic localization and thereby its inert state.…”
Section: Tnf Alpha Induced Proteinmentioning
confidence: 99%
“…In mice, A20‐deficiency causes NF‐κB overactivation and leads to multiorgan inflammation and early lethality 160 . B cell‐specific knockout mice exhibit mild autoimmune disease, whereas dendritic cell specific deletion of A20 induces severe spontaneous inflammation 161‐163 …”
Section: Primarily Inflammationmentioning
confidence: 99%
“…A series of studies have found that DCs participate in liver diseases. Das found that deletion of A20/Tnfaip3 in dendritic cells could promote autoimmune liver pathology to alter T and B-cell homeostasis ( Das et al, 2019 ). Tan et al (2020) demonstrated that hepatic DCs may trigger AIH via a deficiency in canonical Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…A20, the protein encoded by tumor necrosis factor α induced protein 3 ( TNFAIP3 ), can function as a ubiquitin‐editing enzyme (ubiquitin ligase or deubiquitinase) to inhibit nuclear factor kappa‐B (NF‐κB) activation or tumor necrosis factor (TNF)‐mediated NF‐κB independent apoptosis 7,8 . Mice harboring targeted cell‐specific (macrophages, T cells, and B cells) Tnfaip3 deletions will spontaneously develop autoinflammation, which resembles human autoimmune disease 9‐11 . Interferon‐gamma (IFN‐γ) mediated autoreactive CD8 + T cell accumulation is required for epidermal depigmentation.…”
Section: Introductionmentioning
confidence: 99%